THE DIGITAL GATEWAY: HARNESSING FINTECH FOR SME DEVELOPMENT IN UZBEKISTAN’S TRANSITION ECONOMY - Nurmuhammedova Barno Ismailovna; Rakhimboyeva Sugdiyona Rakhimboyevna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: The article examines the influence of digital financing on entrepreneurship and SME development in Uzbekistan’s evolving digital economy. It highlights how initiatives such as the “Digital Uzbekistan 2030” Strategy and the rise of super-app platforms have expanded financial inclusion and accelerated cashless transactions. At the same time, the study notes ongoing barriers to SME growth, including strict collateral requirements, limited financial literacy, cyber risks, and rural connectivity gaps. The paper emphasizes the need to strengthen alternative financing regulations and invest in digital skills and security to support inclusive economic development.